2021
DOI: 10.1111/jfpp.16221
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of different fermentation and cooking methods on dough rheology and the quality of Chinese steamed/baked bread

Abstract: The effects of different fermentation (yeast and sourdough) and cooking (steam and baking) methods on the physicochemical, rheological, and morphological properties of dough, and nutritional property of Chinese steamed/baked bread were investigated. Compared with the yeast‐fermented dough, G′ and G″ were decreased by 18% and 7% for the sourdough‐fermented dough. Compared to the fermented dough, the content of the total amino acid in the corresponding steamed/baked bread was decreased. The content of the essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 25 publications
(26 reference statements)
1
19
0
Order By: Relevance
“…It is generally believed that small molecules of amino acids are more easily digested and absorbed by the human body (Xu et al ., 2021). Rheological properties also confirmed that the gluten degradation in SF was more severe, producing more small molecular proteins, and that the enzyme was easier to act on the protein (Gao et al ., 2022). This result corresponds to the higher amino acid content of CWCSB prepared by SF.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is generally believed that small molecules of amino acids are more easily digested and absorbed by the human body (Xu et al ., 2021). Rheological properties also confirmed that the gluten degradation in SF was more severe, producing more small molecular proteins, and that the enzyme was easier to act on the protein (Gao et al ., 2022). This result corresponds to the higher amino acid content of CWCSB prepared by SF.…”
Section: Resultsmentioning
confidence: 99%
“…Three heat treatment methods, steaming, HTHP, and extrusion, were performed on corn flour as described by Gao et al . (2022) with modifications. Steaming is prepared by putting corn flour into a conical bottle sealed in a steamer for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the storage of breads, the RDS decreased while SDS and RS increased, respectively (Shumoy et al, 2018). Different processing methods will change the physical and chemical characteristics of food, thus affecting human health (Wang & Pang, 2019), the effects of different fermentation (yeast and sourdough) and cooking (steam and baking) methods affect the physicochemical, rheological, and morphological properties of dough, and nutritional property of Chinese steamed/baked bread were investigated (Gao et al, 2021), but studies on the quality of re-heating dough products during different refrigeration time are few reported. In China, steam heating and microwave heating are the most frequent re-heating methods.…”
Section: Introductionmentioning
confidence: 99%